Especiação de compostos de enxofre, níquel e vanádio em cimento asfáltico de petróleo (CAP) e sua relação com os processos de envelhecimento - Sant'Ana, Carla Simone (2015)
The speciation of sulfur compounds in CAP is very important, considering that these compounds are responsible for oxidation processes in asphalt binders, modifying their chemical and physical characteristics. The aim of this work was focused on chemical speciation of sulfur compounds in virgin and aged CAP samples (methods RTFOT, RTFOT/PAV, and RTFOT/SUNTEST) and their maltenic fractions. The separation of sulfur classes were carried out using the method developed by Payzant, which employs specific oxidation reactions and chromatographic separation on silica columns. The studied sulfur compound classes were the following: aromatic/saturated sulfur, aliphatic sulfides, thiophenes and sulfoxides. For this purpose, 6 samples were comparatively analyzed in virgin and aged CAP regarding the distribution of sulfur compounds in the three obtained fractions, where total sulfur was determined in order to observe the compounds behavior in the fractions after different aging processes. After speciation of the compounds, it was observed that the aging process occurs with structural changes in CAP, which involved the break and opening of thiophenic rings and the consequent formation of new S-compounds of high molecular weight. Sulfur compounds in form of sulfoxides increased after aging by RTFOT and RTFOT/PAV. Nickerl and vanadium were also analyzed in the studied samples by GFAAS (maltenic and asphaltenic fractions), since these species are involved in the aging process in CAP. The distribution of Ni and V in asphaltenic and maltenic fractions showed a diminishing of contents of the metals due to the lost by volatilization as metalloporphyrins. Correlating the chemical and physical changes observed in CAP, the variation in viscoelastic properties (G*/sin) may be a reflect of alterations in thiophenic fractions; additionally, variations in the penetration point may be related with the variation in asphaltenes and sulfur compounds of acid/basic characters, what may also be related to the viscoelastic changes in CAP. Based on the obtained results, this work aimed to answer 6 main guiding questions of the thesis: (1) which transformations occur in the speciation of sulfur compounds with the CAP aging after short-term, long-term and UV radiation processes?; (2) what is the major class of sulfur compounds in CAP and how it changes with the aging process?; (3) which transformations occur in the metals nickel and vanadium with CAP aging after short-term, long-term and UV radiation processes?; (4) the forced aging processes for CAP (RTFOT, PAV and SUNTEST) lead to different chemical transformations in asphaltenes and maltenes?; (5) what are the correlations existing between the chemical and physical changes in CAP, from the chemical speciation and rheology after aging process?; (6) is it possible to establish some chemical reactivity order for CAP based on the chemical speciation and rheology after aging process?